Propriedades de medida do LIFE-H 3.1-Brasil para avaliação da participação social de hemiparéticos - de Assumpção, Fernanda Sabine Nunes; de Faria-Fortini, Iza; Magalhães, Lívia de Castro; Basílio, Marluce Lopes; de Carvalho, Augusto Cesinando [UNESP]; Teixeira-Salmela, Luci Fuscaldi (Universidade Federal de Sao Paulo, 2015)
Objective. To evaluate the measurement properties of the LIFE-H 3.1-Brasil, a generic tool for the assessment of social participation, with stroke subjects. Method. The measurement properties were evaluated using Rasch analysis with 109 subjects (58±12 years). Results. In the analysis of the adequacy of the scoring scale, the scoring criteria were not always fully utilized, suggesting that they could be simplified. The principal component analysis of the residuals suggested the presence of at least a second dimension in both sub-scales, which is congruent with the construct of social participation. Although the limit of 5% of erratic items was exceeded for both sub-scales, the elimination of these items is not recommended, since they could be useful with other health conditions, considering that the LIFE-H is a generic instrument. For both the sub-scales ‘Daily activities’ and ‘Social roles’, high levels of reliability and adequate fit with the skill levels of the sample were observed. Conclusion. The LIFE-H 3.1-Brasil measures a multidimensional construct, which requires caution in interpreting its total scores. However, satisfactory measurement properties were found, demonstrating its clinical utility to be applied with stroke subjects with various levels of social participation
Measurement properties of the LIFE-H 3.1-BRASIL for the assessment of social participation after stroke
Keywords: Questionnaires; Reproducibility of results; Social participation; Stroke